Safety assessment of the process quinn packaging, based on erema basic technology, used to recycle post-consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) (2021)
The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Quinn Packaging (EU register number RECYC172). The input is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post-consumer PET containers, with no more than 5% PET from non-food consumer applications. They are heated in a continuous reactor under vacuum before being extruded. Having examined the challenge test provided, the Panel concluded that the continuous reactor step (step 2) is the critical step that determines the decontamination efficiency of the process. The operating parameters to control the performance of this critical step are temperature, pressure and residence time. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.15 μg/kg food, derived from the exposure scenario for toddlers. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern when the final thermoformed trays and containers manufactured with the recycled sheets and not used for packaging water contain up to 100% recycled post-consumer PET. Trays made of this recycled PET are not intended to be used in microwave and conventional ovens and such use is not covered by this evaluation.